Medical aspects of safety of the movement in russian railways - E. A. Zhidkova; E. M. Gutor; M. A. Sorokin; M. R. Kalinin; K. G. Gurevich (Сеченовский вестник, 2018)
Purpose: studying of eﬃciency of medical support of the workers of locomotive crews (WLC) on decrease in the incidence connected with temporary disability.Materials and methods. Data on ﬁve-year incidence (2013-2017) of WLC and costs of JSC "Russian Railways" of their medical maintenance are used. Calculations of the economic losses connected with temporary disability of WLC are executed.Results. The health service of JSC “Russian Railways” works eﬀectively. About 5.9 billion rubles/year are spent for its contents. Due to decrease in the average duration of one case connected with temporary disability, the health service allows to save JSC “Russian Railways” to 5.3 billion rubles annually. Calculation shows that at reduction of a diﬀerence in the average duration of one case of temporary disability in JSC “Russian Railways” and one case of temporary disability for men of working-age of the all-Russian level up to 1.7±0.2 days, the health service can become ineﬃcient from economic positions.Conclusions. From the economic point of view, the health service of JSC “Russian Railways” is justiﬁed at an essential diﬀerence in duration of one case of temporary disability for WLC and temporary disability of the all-Russian level for similar gender and age group.